Impact of Smoking during Pregnancy on Functional Coagulation Testing - Dizon-Townson, Donna; Miller, Connie; Momirova, Valerija; Sibai, Baha; Spong, Catherine Y.; Wendel, George, Jr.; Wenstrom, Katharine; Samuels, Philip; Caritis, Steve; Sorokin, Yoram; Miodovnik, Menachem; O'Sullivan, Mary J.; Conway, Deborah; Wapner, Ronald J.; Gabbe, Steven G. (American Journal of Perinatology, 2012)
Compounds that are systemically absorbed during the course of cigarette smoking, and their metabolites, affect the coagulation system and cause endothelial dysfunction, dyslipidemia, and platelet activation leading to a prothrombotic state. In addition, smoking increases the activity of fibrinogen, homocysteine, and C-reactive protein. We hypothesize that smoking may affect functional coagulation testing during pregnancy. A secondary analysis of 371 women pregnant with a singleton pregnancy and enrolled in a multicenter, prospective observational study of complications of factor V Leiden mutation subsequently underwent functional coagulation testing for antithrombin III, protein C antigen and activity, and protein S antigen and activity. Smoking was assessed by self-report at time of enrollment (<14 weeks). None of the functional coagulation testing results was altered by maternal smoking during pregnancy. Smoking does not affect the aforementioned functional coagulation testing results during pregnancy.
Keywords: coagulation; smoking; pregnancy; factor V Leiden